Experiences in using a multiparadigm and multiprogramming approach to teach an information systems course on introduction to programming - Gutiérrez Cárdenas, Juan Manuel (2020)
In the current literature, there is limited evidence of the effects of teaching programming languages using two different paradigms concurrently. In this paper, we present our experience in using a multiparadigm and multiprogramming approach for an Introduction to Programming course. The multiparadigm element consisted of teaching the imperative and functional paradigms, while the multiprogramming element involved the Scheme and Python programming languages. For the multiparadigm part, the lectures were oriented to compare the similarities and differences between the functional and imperative approaches. For the multiprogramming part, we chose syntactically simple software tools that have a robust set of prebuilt functions and available libraries. After our experiments, we found that the students were strongly biased towards memorizing the syntax of these languages, jeopardizing their ability to learn to think algorithmically and logically in order to solve the given problems. We believe that teaching students using multiparadigm and multiprogramming techniques could be discouraging, especially for those students with no programming experience. In this research study, we present the results of applying this approach together with the achievements, failures, and trends of the students who were taught with this multipath system.